The Ubiquitin-Proteasome System in Huntington’s Disease: Are Proteasomes Impaired, Initiators of Disease, or Coming to the Rescue? - Sabine Schipper-Krom; Katrin Juenemann; Eric A. J. Reits (Biochemistry Research International)
Huntington’s disease is a progressive neurodegenerative disease, caused by a polyglutamine expansion in the huntingtin protein. A prominent hallmark of the disease is the presence of intracellular aggregates initiated by N-terminal huntingtin fragments containing the polyglutamine repeat, which recruit components of the ubiquitin-proteasome system. While it is commonly thought that proteasomes are irreversibly sequestered into these aggregates leading to impairment of the ubiquitin-proteasome system, the data on proteasomal impairment in Huntington’s disease is contradictory. In addition, it has been suggested that proteasomes are unable to actually cleave polyglutamine sequences in vitro, thereby releasing aggregation-prone polyglutamine peptides in cells. Here, we discuss how the proteasome is involved in the various stages of polyglutamine aggregation in Huntington’s disease, and how alterations in activity may improve clearance of mutant huntingtin fragments.